PROFESIONAL GURU DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMAS St. PETRUS KEWAPANTE - Mutia Malmar; Kartini Rahman Nisa (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
The purpose of this study is to confirm and analyze the professionalism of teachers at SMAS ST. Petrus Kewapante, which includes teachers' understanding of professionalism, its implementation in learning activities, and various obstacles encountered in carrying out their duties as professional educators. Data in this study were collected using instruments such as observation, documentation, and in-depth interviews. The research subject was one (1) physics teacher at SMAS ST. Petrus Kewapante who was selected as the main informant. The data were analyzed using descriptive qualitative analysis techniques with the following stages: data reduction (sorting and focusing data according to the research objectives), data presentation (systematically compiling data in narrative form), and drawing conclusions and verification (interpreting the meaning of the data to obtain research findings). The results of the study indicate that teachers at SMAS ST. Petrus Kewapante have internalized the values of professionalism, as seen in their ability to plan and implement learning in accordance with the characteristics of the students, their deep mastery of the subject matter, their attitudes and personalities that reflect exemplary behavior, and their ability to build effective communication with students and the school environment. ABSTRAK Tujuan penelitian ini adalah untuk menegaskan dan menganalisis profesionalisme guru di SMAS ST. Petrus Kewapante, yang mencakup pemahaman guru tentang profesionalisme, bentuk implementasinya dalam kegiatan pembelajaran, serta berbagai hambatan yang dialami dalam menjalankan tugas sebagai pendidik profesional. Data dalam penelitian ini dikumpulkan menggunakan instrumen berupa observasi, dokumentasi, dan wawancara mendalam. Subjek penelitian berjumlah 1 (satu) orang guru Fisika di SMAS ST. Petrus Kewapante yang dipilih sebagai informan utama. Data dianalisis menggunakan teknik analisis kualitatif deskriptif dengan tahapan: Reduksi data (memilah dan memfokuskan data sesuai tujuan penelitian), Penyajian data (menyusun data secara sistematis dalam bentuk narasi), dan Penarikan kesim  pulan serta verifikasi (menafsirkan makna data untuk memperoleh temuan penelitian). Hasil penelitian menunjukkan bahwa guru di SMAS ST. Petrus Kewapante telah menginternalisasi nilai-nilai profesionalisme yang terlihat dari kemampuannya merencanakan dan melaksanakan pembelajaran sesuai dengan karakteristik peserta didik, penguasaan materi pelajaran yang mendalam, sikap dan kepribadian yang mencerminkan keteladanan, serta kemampuannya membangun komunikasi yang efektif dengan siswa maupun lingkungan sekolah.